Skin mediated human papillomavirus infection in breast: A report of four cases - Islam, Saimul; Dasgupta, Hemantika; Basu, Mukta; Roy, Anup; Alam, Neyaz; Mandal, Gautam Kumar; Roychoudhury, Susanta; Panda, Chinmay Kumar (Indian Journal of Case Reports, 2018)
To address the ambiguity of different modes of human papillomavirus (HPV) transmission in breast, the immunohistochemical expression of two oncoproteins E6/E7 of HPV16 was analyzed in primary breast cancer (BC) and adjacent normal skin of 4 samples. The patients were of 35–55 years old having no previous history of cancer. The E6/E7 expressions were evident in both skin and BC. In skin, high/moderate cytoplasmic expressions of E6/E7 proteins were seen in all samples, whereas in BC, high/moderate cytoplasmic expressions of the proteins were observed in 2–3 samples. Thus, it seems that HPV infection in the breast may occur through the skin.